Acute changes in haematocrit leading to polycythaemia in late-onset hypogonadism patients that receive testosterone replacement therapy: a South African study. Issue 2 (4th May 2019) - du Plessis, Jesslee; Bester, Hermanus Lambertus; Julyan, Marlene; Cockeran, Marike
Abstract : Background: According to the literature, parenteral testosterone replacement therapy (TRT)-induced polycythaemia is associated with cardiovascular events. No or minimal data exist for the prevalence of TRT-induced polycythaemia in late-onset hypogonadism (LOH) patients from South Africa. Polycythaemia is the side effect most frequently associated with parental TRT formulations. Design: This was a quantitative, observational, descriptive, retrospective study. Setting: The study setting was a private practice male clinic in Emalahleni. Subject: An all-inclusive sampling method was used. Outcome measures: The main outcome measure for polycythaemia was haematocrit (Hct). An Hct percentage of > 50% at month 3 (post-treatment initiation) constituted a positive diagnosis for polycythaemia. For the rise in total testosterone (TT) and Hct, the variance was used as documented between pre- and post-treatment initiation. Results: The prevalence of polycythaemia was 34%. A statistically significant increase in both TT and Hct was observed. The Cohen's d effect size was 0.68 and 0.73, respectively, for TT and Hct. Conclusion: Depot-testosterone undecanoate parenteral formulation induces polycythaemia in LOH patients, where the rise in TT demonstrates the effectiveness of therapy.